Significance of serum angiogenin assay as a novel marker for diagnosis of hepatocellular carcinoma in liver cirrhosis: a comparative study. Issue 1 (January 2015) - Adel, Nanees A.; Kaisar, Hany H.; Khayyal, Ahmad E.; Sabbour, Ghada M.S.; Mahmoud, Nermine H.; Ahmed, Hala A.
Abstract : Background: Hepatocellular carcinoma (HCC) is the third most common cause of cancer-related death worldwide. Angiogenin (ANG) is a potent angiogenic factor first isolated from the culture medium conditioned by colon carcinoma cells. Many reports have demonstrated an elevated serum ANG level in patients with various malignancies including colorectal carcinoma, melanoma, and pancreatic carcinoma. These results pointed to serum ANG as a novel marker for the diagnosis, progression, and aggressiveness of malignant tumors. Objective: The aim of this study was to evaluate the clinical significance of serum ANG as a novel marker for the diagnosis of HCC in liver cirrhosis and compare it with serum α-fetoprotein (AFP). Patients and methods: The study included 40 patients who were divided into group I and group II. Group I included patients with HCC and group II included those with liver cirrhosis. Group III included age-matched and sex-matched apparently healthy controls. Patients in group I were further classified according to the TNM system into subgroup Ia, which included patients with tumor size less than or equal to 2 cm, and subgroup Ib, which included patients with tumor size greater than 2 cm. All individuals were subjected to an assay for evaluating the serum level of AFP and serum ANG. Results: For the diagnosis of HCC, serum AFP showed a sensitivity of 91.7% and specificity of 80%, whereas serum ANG showed a sensitivity of 95.8% and specificity of 85.7%. In discriminating patients with early hepatic cancer from those with more advanced stages, serum AFP showed a diagnostic sensitivity of 70% and specificity of 89.8%, whereas serum ANG showed a diagnostic sensitivity of 90% and specificity of 85.7%. Conclusion: Serum ANG is a promising marker for the diagnosis of HCC, being superior to serum AFP in both sensitivity and specificity. Moreover, serum ANG efficiently discriminates early from late stages of HCC.